Solution NMR structure of RHE_CH02687 from Rhizobium etli: A novel flavonoid‐binding protein. Issue 5 (16th February 2017) - Liang, Chunjie; Zhu, Jiang; Hu, Rui; Ramelot, Theresa A.; Kennedy, Michael A.; Liu, Maili; Yang, Yunhuang
ABSTRACT: We report the solution NMR structure of RHE_CH02687 from Rhizobium etli . Its structure consists of two β‐sheets that together with two short and one long α‐helix form a hydrophobic cavity. This protein shows a high structural similarity to the prokaryotic protein YndB from Bacillus subtilis, and the eukaryotic protein Aha1. NMR titration experiments confirmed that RHE_CH02687, like its homolog YndB, interacted with flavonoids, giving support for a biological function as a flavonoid sensor in the symbiotic interaction between R. etli and plants. In addition, our study showed no evidence for a direct interaction between RHE_CH02687 and HtpG, the R. etli homolog of Hsp90. Proteins 2017; 85:951–956. © 2016 Wiley Periodicals, Inc.